Unilateral ectopic breast tissue in the vulva - A diagnostic dilemma - Dashora Sanchita; Joshi Ruchi (Wolters Kluwer Medknow Publications, 2023)
Ectopic breast tissue is a rare condition caused by remnants of the mammary ridges that fail to involute during embryologic development. Clinical presentation of vulval breast tissue is highly variable and diagnosis is ultimately made by tissue biopsy and histopathological examination. Since this ectopic tissue serves no function, surgical excision is recommended. Vulval ectopic breast tissue is an extremely rare case, especially in midlife. Because of its rarity in occurrence and unusual site, here we report a case of unilateral ectopic breast tissue on the vulva in an adult midlife female.